SISTEM PENDUKUNG KEPUTUSAN TENDER PROYEK MENGGUNAKAN METODE BENEFIT COST RATIO - Rukmana, Siti Hardiyanti (JST (Jurnal Sains dan Teknologi), 2016)
The procurement process became one of the important aspects for PT. PLN (Persero) to operate the company. One way to meet these needs is through the project tender. The tender process aims to get high-grade materials with the lowest prices that meet the criteria of efficiency PT. PLN (Persero). In order to simplify the bidding process required a decision support system. The method used in this system is Benefit Cost Ratio (BCR). Input in this application are the documents and the tender offer price from bidders with complete tender documents that have been validated by prospective bidders and then selected by the tender committee to make an assessment and validation winner. The output of this process is the winner of the tender project based on calculations Benefit Cost Ratio (BCR). Therefore, the method Benefit Cost Ratio (BCR) can be used as a decision support system to determine the winner of the project tender.